Economic Role of Vegetable Farming in Tharu Women’s Livelihoods in Chitwan, Nepal - Khanal , Tantrika Raj; Raut , Rekha; Katuwal, Khadga Bahadur (Educational Journal, 2024)
This study investigates how Tharu women make a decision-making basis with regard to vegetable economy in Chitwan District, Nepal. It brings out the point that they are hard workers in agriculture, but they do not have significant access to the economy. Their ability to regulate their income, their economic condition in general, and the part they play in selling and raising vegetables are the aspects that the study examines. It utilizes quantitative and qualitative information. Surveying 267 Tharu women farmers and discussing the issue with the community leaders allowed for obtaining more in-depth information. Multilinear regression was one of the techniques that the data using basic statistics. As the findings indicate, even though the Tharu women contribute so much in farming activities such as weeding (85.4%) and harvesting (78%), they do not have a big say in the distribution of farming income. There are only 11.6 percent who own the land to cultivate, and only about 15 percent market the crops or manage financial affairs. Nevertheless, agriculture provides about NPR 195,400 to a family in a year on average. It can be analysed that having a larger piece of land (0.45) and whether someone is trained when it comes to farming (0.28) play an important role in increasing household income. In sum, the research shows that, despite the importance of farming to their lives, Tharu women do not enjoy the decisional power because of the structural factors. The substantial change is possible only in the case of agricultural work improved; women have to be able to sell their crops, have control over land, and make financial decisions.